Efficient Taxation of Fuel and Road Use - Geir H. M. Bjertnæs (Center for Economic Studies and ifo Institute (CESifo), 2019)
This study calculates efficient taxes on gasoline and road use designed to combat driving related externalities when motorists avoid taxes due to an excessive economic driving-style. The efficient tax on gasoline is reduced below the Pigouvian rate due to such avoidance. The current US tax rate on gasoline is below the efficient tax rate while the current UK rate is slightly above the efficient rate in this case. A GPS-based road user charge prevents such avoidance. The efficient GPS-based road user charge should be combined with a tax on gasoline which promotes an economic driving-style that lowers accidents.
Keywords: H20; H21; H23; Q58; R48; 330; transportation; optimal taxation; environmental taxation; global warming